Nanofiltration membrane, method for preparing nanofiltration membrane from isoparaffin solvent and application of nanofiltration membrane
By using the interface polymerization of isomer alkanes and amino aqueous phase, a nanofiltration membrane with good chlorine resistance is formed, which solves the problems of flammable, explosive and poor chlorine resistance in traditional nanofiltration membranes, and achieves safer production and higher Ion retention rate.
Patent Information
- Application Number
- CN202411215640.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-31
- Publication Date
- 2024-12-31
AI Technical Summary
Chemicals such as n-hexane and cyclohexane used in the preparation of existing nanofiltration membranes are flammable and explosive, resulting in complex production environments and high risks, and poor chlorine resistance in the functional layer.
Isomer alkanes such as isomer decane, isomer dodecane, isomer tridecane, isomer tridecane, isomer tritetradecane, etc. are used as solvents to form a nanofiltration membrane with good chlorine resistance through interface polymerization with amino aqueous solution. , replaces traditional organic phase monomers.
A safer production process is achieved, the chlorine resistance and ion retention rate of the nanofiltration membrane are improved, and the process flow is simplified, making it suitable for automated production.
Smart Images

Figure BDA0005021479420000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of separation, and specifically relates to a nanofiltration membrane and a method and application of preparing the nanofiltration membrane with an isoparaffin solvent. Background Art
[0002] In the existing technology of nanofiltration membrane, the functional layer is generally prepared by the interfacial polymerization of aqueous phase monomers and organic phase monomers, wherein the aqueous phase monomers generally use chemicals such as n-hexane and cyclohexane. Since such chemicals are currently flammable and explosive and are classified as hazardous chemicals, they need to comply with various safety requirements during the procurement and use processes. There are also relevant explosion-proof requirements for the production equipment of nanofiltration membranes, drug storage warehouses, and the explosion-proof of the production workshop buildings themselves. The preparation environment requirements for nanofiltration membranes are relatively complex, and the risks in the preparation process are also relatively high. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a nanofiltration membrane and a method and application of preparing the nanofiltration membrane using an isoparaffin solvent.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] A method for preparing a nanofiltration membrane with an isoalkane solvent comprises the following steps: coating an amino aqueous phase solution on the surface of a base membrane, and performing an interfacial polymerization reaction with an organic phase solution after sufficient coating and infiltration; the solvent of the organic phase solution is an isoalkane.
[0006] The isomeric alkanes are isomeric decanes, isomeric dodecanes, isomeric tridecanes, isomeric tetradecanes and isomeric hexadecanes.
[0007] The amino aqueous phase solution is one of piperazine and polyethyleneimine or a mixture thereof.
[0008] The concentration of the amino aqueous solution is 0.5-2.5%, preferably 1.5%.
[0009] The solute of the organic phase solution is trichloroisocyanuric acid.
[0010] The concentration of the organic phase solution is 0.1-0.5%, preferably 0.2%.
[0011] The base film is one of polysulfone, polyvinylidene fluoride or polyvinyl chloride.
[0012] The method for preparing a nanofiltration membrane with an isoalkane solvent comprises the following steps: at room temperature, first immersing the base membrane filaments in an organic phase solution with an isoalkane as solvent to ensure that the surface of the membrane filaments is fully wetted, then using a fan to sweep the surface of the membrane filaments to ensure that the organic phase solution is evenly distributed on the surface of the membrane filaments; then the swept membrane filaments are pulled into an aqueous phase solution for full wetting; finally, the membrane filaments completely wetted with the aqueous phase solution are pulled into an oven for polymerization to obtain a nanofiltration membrane; preferably, the polymerization temperature is 40-80°C; preferably 60°C; the polymerization time is 4-20min; preferably 8min.
[0013] The present invention also includes a nanofiltration membrane obtained by the method.
[0014] The present invention also includes an application of the nanofiltration membrane.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The technical solution of this application uses isoalkane solvents to replace hazardous chemicals such as n-hexane and cyclohexane, and the process is safer. As a preferred method, the isoalkane is used for the interfacial polymerization of trichloroisocyanuric acid and amino groups, because it does not contain active hydrogen groups and has good chlorine resistance; the technical solution of this application has a simple process and can use existing process designs and equipment to achieve automated production. DETAILED DESCRIPTION
[0017] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments.
[0018] A method for preparing a nanofiltration membrane using an isoalkane solvent comprises the following steps: coating an amino aqueous phase solution on the surface of a base membrane, and then subjecting the base membrane to an interfacial polymerization reaction with an organic phase solution after sufficient coating and infiltration; the solvent of the organic phase solution is an isoalkane. The isoalkane is isodecane, isododecane, isotridecane, isotetradecane and isohexadecane. The amino aqueous phase solution is one of piperazine or polyethyleneimine or a mixture thereof; the solute of the organic phase solution is trichloroisocyanuric acid. The base membrane is one of polysulfone, polyvinylidene fluoride, or polyvinyl chloride.
[0019] Specifically, the following steps are included: at room temperature, the base membrane filaments are first immersed in an organic phase solution with isoalkane as solvent to ensure that the surface of the membrane filaments is fully wetted, and then the surface of the membrane filaments is swept by a fan to ensure that the organic phase solution is evenly distributed on the surface of the membrane filaments; the purged membrane filaments are then pulled into the aqueous phase solution for full wetting; finally, the membrane filaments completely soaked in the aqueous phase solution are pulled into an oven for polymerization to obtain a nanofiltration membrane; preferably, the polymerization temperature is 40-80°C; preferably 60°C; the polymerization time is 4-20min; preferably 8min.
[0020] The following examples are used for illustration.
[0021] Example 1
[0022] At room temperature, the base membrane PVDF hollow fiber membrane filament was first immersed in a stainless steel tank filled with a 0.1wt% trichloroisocyanuric acid organic solution with isohexadecane as solvent by a drawing machine. The process control ensured that the outer surface of the hollow fiber membrane was wetted for 60s. Then, the hollow fiber membrane was pulled from top to bottom at an angle perpendicular to the ground to a cross-sectional area of 0.25m 2 The pipe is filled with air and the fan is used to blow air at 0.5m 3 The surface of the hollow fiber membrane is purged from bottom to top at a flow rate of 500 μg / min for 15 seconds to ensure that the trichloroisocyanuric acid solution is evenly distributed on the surface of the hollow fiber membrane; the purged membrane fibers are then pulled into a stainless steel tank filled with a 0.5 wt% piperazine aqueous solution, and the outer surface of the hollow fiber membrane is ensured to be wetted for 60 seconds through process control; finally, the hollow fiber membrane completely soaked in the piperazine aqueous solution is pulled into an oven at 60°C and dried for 8 minutes to obtain a hollow fiber nanofiltration membrane, and the prepared hollow fiber nanofiltration membrane is immersed in deionized water for standby use.
[0023] Embodiment 2-10
[0024] The difference between Example 2-10 and Example 1 is that the type of amino group in the aqueous solution, the amino group concentration, and the solubility of the organic phase are adjusted, as shown in Table 1.
[0025] Table 1
[0026] Example Isoalkanes Amino Type Amino concentration (%) Organic phase concentration (%) 1 Isomeric Hexadecane Piperazine 0.5 0.1 2 Isomeric Hexadecane Piperazine 1.0 0.1 3 Isomeric Hexadecane Piperazine 1.5 0.1 4 Isomeric Hexadecane Piperazine 2 0.1 5 Isomeric Hexadecane Piperazine 2.5 0.1 6 Isomeric Hexadecane Piperazine 1.5 0.2 7 Isomeric Hexadecane Piperazine 1.5 0.3 8 Isomeric Hexadecane Piperazine 1.5 0.4 9 Isomeric Hexadecane Piperazine 1.5 0.5 10 Isomeric Hexadecane Polyethyleneimine 1.0 0.2
[0027] Comparative Example 1
[0028] At room temperature, the base membrane PVDF hollow fiber membrane was first immersed in a stainless steel tank filled with a 0.5wt% trimesoyl chloride organic solution with n-hexane as the solvent by a drawing machine. The process control ensured that the outer surface of the hollow fiber membrane was wetted for 30s. Then, the hollow fiber membrane was pulled from top to bottom at an angle perpendicular to the ground to a cross-sectional area of 0.5m 2 The pipe is filled with air and the fan is used to blow air at 0.5m 3 The surface of the hollow fiber membrane is purged from bottom to top at a flow rate of 500 μg / min for 15 seconds to ensure that the trimesoyl chloride solution is evenly distributed on the surface of the hollow fiber membrane; the purged membrane fibers are then pulled into a stainless steel tank filled with a 3.0 wt% piperazine aqueous solution, and the outer surface of the hollow fiber membrane is ensured to be wetted for 60 seconds through process control; finally, the hollow fiber membrane completely soaked in the piperazine aqueous solution is pulled into an oven at 40°C and dried for 5 minutes to obtain a hollow fiber nanofiltration membrane, and the prepared hollow fiber nanofiltration membrane is immersed in deionized water for standby use.
[0029] The nanofiltration membrane obtained in the above embodiment was made into a membrane assembly by static casting for effect testing, and the results are shown in Table 2. The membrane assembly was fixed on a cross-flow filtration test device, and pure water passed through the membrane assembly under external pressure mode. The pressure of the cross-flow filtration test device was set at 0.4MPa and pre-pressed for 1h to fully compact the membrane, and then the following tests were performed: ① The cross-flow filtration test device was operated at a pressure of 0.3MPa with pure water as the feed liquid, and pure water passed through the membrane assembly in the external pressure mode, and the water obtained within 10min was collected, and the pure water flux was tested using the weighing method. ② The cross-flow filtration test device was operated at a pressure of 0.3MPa, with 1000mg / L MgCl2 solution as the feed liquid for testing, and the salt solution passed through the membrane assembly under external pressure mode. The salt concentration in the produced water was tested using a conductivity meter every 10min until it was stable and unchanged to obtain the retention rate. ③ Soak the membrane assembly in a 1000 mg / L NaClO aqueous solution for 1 h, then take it out and test the retention rate of a 1000 mg / L MgCl2 solution in the same manner as in ②.
[0030] Table 2
[0031]
[0032] Result analysis:
[0033] Different isomeric alkanes are used as solvents to replace n-hexane and cyclohexane to complete interfacial polymerization, which makes the process safer and is also applied to the polymerization of trichloroisocyanuric acid and amino aqueous phase.
[0034] It can be seen from Examples 1 to 5 that when the piperazine content in the aqueous phase is increased from 0.5% to 1.5%, the retention rate of the obtained nanofiltration membrane for MgCl2 increases while the membrane flux decreases. Due to the increase in the piperazine concentration, piperazine is more likely to undergo polymerization reaction with trichloroisocyanuric acid, which can not only increase the rate of the polymerization reaction, but also help to improve the network crosslinking degree of the obtained polymer, and the formed functional layer is more complete; however, when the piperazine content is further increased to 2.5%, the retention rate of the obtained hollow fiber nanofiltration membrane for MgCl2 decreases instead of increases. This is because the excessive concentration of isopiperazine causes the polymerization reaction rate to be too fast, and the obtained polymer is sparse and disordered, and with the rapid superposition of the thickness of the functional layer, the resistance of piperazine to diffuse into the organic phase increases, which in turn leads to a decrease in the polymerization rate and the degree of polymer crosslinking, resulting in a decrease in the ion retention rate of the nanofiltration membrane and an increase in the flux.
[0035] It can be seen from Example 1 and Example 6-Example 9 that when the trichloroisocyanuric acid content in the organic phase is increased from 0.1% to 0.2%, the interception rate of the obtained nanofiltration membrane for MgCl2 increases and the membrane flux decreases. Due to the increase in the concentration of trichloroisocyanuric acid in the solution, piperazine is easy to undergo polymerization reaction with trichloroisocyanuric acid, which accelerates the polymerization reaction rate and improves the cross-linking degree of the polymer network. The functional layer is more uniform and dense, and the ion interception rate of the composite nanofiltration membrane is improved. However, when the trichloroisocyanuric acid content in the organic phase is further increased from 0.2% to 0.5%, the interception rate of the obtained composite nanofiltration membrane decreases instead. This is because the excessive concentration of trichloroisocyanuric acid in the organic phase causes the obtained polymer to be sparse and disordered, and with the rapid superposition of the thickness of the functional layer, the resistance of piperazine to diffuse into the organic phase increases, which then leads to a decrease in the polymerization rate and the degree of cross-linking of the polymer, so that the ion interception rate of the nanofiltration membrane is reduced and the flux is increased.
[0036] From Example 6, Example 10 and Comparative Example 1 and Comparative Example 2, it can be seen that the nanofiltration membrane obtained by changing the organic phase to trichloroisocyanuric acid is comparable to the nanofiltration membrane obtained by traditional use of trimesoyl chloride in the conventional state for MgCl2 retention rate. However, after being soaked in sodium hypochlorite solution, since the functional layer of the traditional polyamide nanofiltration membrane contains active hydrogen groups (such as -NH-CO-), it is easily oxidized by active chlorine such as hypochlorite to produce aromatic substitution reaction or N-chlorination reaction, resulting in functional layer integrity destruction, and the ion retention rate is greatly reduced. This conclusion can also be confirmed by the detection data of Comparative Examples 1 and 2. However, there is no active hydrogen in the nanofiltration membrane obtained by interfacial polymerization reaction using trichloroisocyanuric acid as the organic phase, and the molecular steric hindrance is large, which greatly improves the chlorine resistance of the nanofiltration membrane. It can also be seen from the detection data that the composite nanofiltration membrane obtained in Example 1 and Example 6 has no obvious change in retention rate after soaking in 1000mg / L NaClO aqueous solution for 1h, indicating that the membrane itself has obvious chlorine resistance.
[0037] In summary, the technical solution of this application uses isoparaffin solvents to replace hazardous chemicals such as n-hexane and cyclohexane, and the process is safer. The isoparaffin is applied to the interfacial polymerization of trichloroisocyanuric acid and amino groups. Since it does not contain active hydrogen groups, it has good chlorine resistance. The technical solution of this application has a simple process and can use existing process designs and equipment to achieve automated production.
[0038] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a nanofiltration membrane using an isoparaffin solvent, characterized in that: The method comprises the following steps: coating an amino aqueous phase solution on the surface of a base film, and performing an interfacial polymerization reaction with an organic phase solution after the surface is fully coated and infiltrated; the solvent of the organic phase solution is isomeric alkane.
2. The method for preparing a nanofiltration membrane using an isoparaffin solvent according to claim 1, characterized in that: The isomeric alkanes are isomeric decanes, isomeric dodecanes, isomeric tridecanes, isomeric tetradecanes and isomeric hexadecanes.
3. The method for preparing a nanofiltration membrane using an isoparaffin solvent according to claim 1, characterized in that: The amino aqueous phase solution is one of piperazine and polyethyleneimine or a mixture thereof.
4. The concentration of the amino aqueous solution according to claim 1 is 0.5-2.5%, preferably 1.5%.
5. The method for preparing a nanofiltration membrane using an isoparaffin solvent according to claim 1, characterized in that: The solute of the organic phase solution is trichloroisocyanuric acid.
6. The method for preparing a nanofiltration membrane using an isoparaffin solvent according to claim 1, characterized in that , the concentration of the organic phase solution is 0.1-0.5%; preferably 0.2%.
7. The method for preparing a nanofiltration membrane using an isoparaffin solvent according to claim 1, characterized in that , the base membrane is one of polysulfone, polyvinylidene fluoride, or polyvinyl chloride.
8. The method for preparing a nanofiltration membrane using an isoparaffin solvent according to claim 1, characterized in that , including the following steps: at room temperature, immersing the membrane filaments of the base membrane in an organic phase solution with isoalkane as solvent to ensure that the surface of the membrane filaments is fully wetted, and then using a fan to blow the surface of the membrane filaments to ensure that the organic phase solution is evenly distributed on the surface of the membrane filaments; then the purged membrane filaments are pulled into the aqueous phase solution for full wetting; finally, the membrane filaments completely soaked in the aqueous phase solution are pulled into an oven for polymerization to obtain a nanofiltration membrane; preferably, the polymerization temperature is 40-80°C; preferably 60°C; the polymerization time is 4-20min; preferably 8min.
9. A nanofiltration membrane obtained by the method according to any one of claims 1 to 8.
10. Use of the nanofiltration membrane according to claim 9.
